Penanganan Terhadap Tindak Pidana Pemerkosaan Anak di Bawah Umur - Nur Hijrah Zainuddin; Moh.R.U. Puluhulawa; Nuvazria Achir (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out how the crime of raping minors is handled. This research is empirical legal research by presenting field facts as the main data, which are then analyzed descriptively qualitatively. The research results show that the handling of criminal acts, especially those related to sexual intercourse, is usually left to the parents of the victim or perpetrator. The sexual intercourse referred to is when the perpetrator and victim have sexual relations on the basis of mutual consent and it is disputed by the victim's family. What is the PPA unit of the Gorontalo City Police doing in terms of making peace efforts, because considering that the perpetrators of this crime are still children, protection measures must also be taken so that the children can grow and develop and return to normal activities in society. This handling includes receiving complaint reports, the investigation and case investigation stage, the file transfer stage and providing protection for victims. Law enforcers need to consider implementing the concept of restorative justice in minor cases in accordance with existing provisions, but not in cases of rape or sexual violence, especially against children. Apart from that, the community, especially parents and families, are as far as possible against peace efforts to marry the victim to the perpetrator, because it can trigger other problems and prevent repetition of criminal acts and other violence that the victim will receive.